2019
DOI: 10.1088/1751-8121/ab2f46
|View full text |Cite
|
Sign up to set email alerts
|

Real-space renormalization-group methods for hierarchical spin glasses

Abstract: We focus on two real-space renormalization-group (RG) methods recently proposed for a hierarchical model of a spin glass: A sample-by-sample method, in which the RG transformation is performed separately on each disorder sample, and an ensemble RG (ERG) method [M. C. Angelini, G. Parisi, and F. Ricci-Tersenghi. Ensemble renormalization group for disordered systems. Phys. Rev. B, 87(13):134201, 2013] in which the transformation is based on an average over samples. Above the upper critical dimension, the sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(38 citation statements)
references
References 27 publications
0
37
1
Order By: Relevance
“…which is, in general, different from one, and which corresponds to the value in Fig. 5a of [3] which is reached by…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…which is, in general, different from one, and which corresponds to the value in Fig. 5a of [3] which is reached by…”
mentioning
confidence: 71%
“…where σ t 1 1 and σ t 2 1 are the standard deviations of the spin couplings at the first hierarchical level of the hierarchical Edwards-Anderson model (HEA), at the t-th ensemble renormalization group (ERG) step, and at inverse temperatures β 1 and β 2 , respectively. However, in [3] we have shown that…”
mentioning
confidence: 85%
See 3 more Smart Citations